Traditional Chinese acupuncture versus minimal acupuncture for mild-to-moderate knee osteoarthritis: a protocol for a randomised, controlled pilot trial. Issue 12 (13th December 2016) - Sun, Ning; Shi, Guang-Xia; Tu, Jian-Feng; Li, Yong-Ting; Zhang, Li-Wen; Cao, Yan; Du, Yi; Zhao, Jing-Jie; Xiong, Da-Chang; Hou, Hai-Kun; Liu, Cun-Zhi
Abstract : Introduction: Knee osteoarthritis (KOA) is one of the most common musculoskeletal disorders. Acupuncture is a popular form of complementary medicine for musculoskeletal conditions, although the evidence is inconclusive. Our objective is to evaluate the efficacy of traditional Chinese acupuncture for pain relief and function improvement in mild-to-moderate knee osteoarthritis (TCAKOA) participants. Methods/analysis: 42 patients will be recruited who have been diagnosed with mild-to-moderate KOA and randomly allocated in equal proportions to traditional Chinese acupuncture or minimal acupuncture. They will receive acupuncture for 24 sessions over 8 weeks. The primary end point is success rate, which will be calculated according to a change from baseline in Western Ontario and McMaster Universities Osteoarthritis Index pain and function scores at 8 weeks. Secondary end points include pain and function measurement, global change, the quality of life and the use of non-steroidal anti-inflammatory drugs (Celebrex, Pfizer) at 8, 16 and 26 weeks. Ethics and dissemination: Ethical approval of this study has been granted by the Research Ethical Committee of Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University (permission number: 2016BL-010-02). Written informed consent will be obtained from all participants. Outcomes of the trial will be disseminated through peer-reviewed publications. Trial registration number: ISRCTN14016893; Pre-results.